Assessment of a multi-species in situ FTIR for precise atmospheric greenhouse gas observations - Hammer, Samuel; Konrad, Gerrit; Vardag, Sanam Noreen; Levin, Ingeborg (Atmospheric measurement techniques, 2013)
We thoroughly evaluate the performance of a multi-species, in situ Fourier transform infrared (FTIR) analyser with respect to high-accuracy needs for greenhouse gas monitoring networks. The in situ FTIR analyser is shown to measure CO2, CO, CH4 and N2O mole fractions continuously, all with better reproducibility than the inter-laboratory compatibility (ILC) goals, requested by the World Meteorological Organization (WMO) for the Global Atmosphere Watch (GAW) programme. Simultaneously determined δ13CO2 reaches reproducibility as good as 0.03‰. Second-order dependencies between the measured components and the thermodynamic properties of the sample, (temperature, pressure and flow rate) and the cross sensitivities among the sample constituents are investigated and quantified. We describe an improved sample delivery and control system that minimises the pressure and flow rate variations, making post-processing corrections for those quantities non-essential. Temperature disequilibrium effects resulting from the evacuation of the sample cell are quantified and improved by the usage of a faster temperature sensor. The instrument has proven to be linear for all measured components in the ambient concentration range. The temporal stability of the instrument is characterised on different time scales. Instrument drifts on a weekly time scale are only observed for CH4 (0.04 nmol mol−1 day−1) and δ13CO2 (0.02‰ day−1). Based on 10 months of continuously collected quality control measures, the long-term reproducibility of the instrument is estimated to ±0.016 μmol mol−1 CO2, ±0.03‰ δ13CO2, ±0.14 nmol mol−1 CH4, ±0.1 nmol mol−1 CO and ±0.04 nmol mol−1 N2O. We propose a calibration and quality control scheme with weekly calibrations of the instrument that is sufficient to reach WMO-GAW inter-laboratory compatibility goals.